EFFECTIVENESS OF MEDIATION IN OUT-OF-COURT SETTLEMENT OF INHERITANCE DISPUTES - Izzati, Nida Rafiqa; Arfa, M Fadhil Azzam; Pebriansyah, Taufik Pajar; Na’im, Arroyan; Asnawi, M. Natsir (PT. Altin Riset Publishing, 2024)
This research discusses the effectiveness of mediation in settling inheritance disputes outside of the court. The objectives of this study are, firstly, to determine the effectiveness of mediation in resolving inheritance disputes outside of court; secondly, to assess whether conducting mediation outside of court is a viable solution in settling inheritance disputes; thirdly, to identify the factors that contribute to the success of mediation in resolving inheritance disputes outside of court. The research method employed in this discussion is library research, supplemented with analytical descriptive data analysis. Based on the research findings, mediation has proven its effectiveness in settling inheritance disputes outside of court. By expediting the resolution process, reducing costs, and enhancing the satisfaction of the involved parties, mediation presents an attractive alternative worthy of consideration as a solution in settling inheritance disputes through non-litigious means. Another evidence demonstrating the effectiveness of mediation conducted outside of court is its greater impact in maintaining positive relationships, as the outcome is not a win-lose decision, but rather a win-win situation where both parties equally win and willingly accept the agreed-upon settlement, in line with the principles of win-win solutions.